Peran Komitmen Science Based Target Initiatives dalam Memoderasi Pengaruh Tingkat Emisi Gas Karbon terhadap Kinerja Keuangan Perusahaan (Studi Pada Negara Maju dan Berkembang Kawasan Asia Pasifik) - Munandar Isna Septian A; Harjum Muharam (Faculty of Economics and Business Diponegoro University, 2025)
Climate change presents a real threat to global ecosystems and economic activities, marked by rising global temperatures, extreme weather, and sea-level rise. With 2023 recorded as the hottest year since 1850, the urgency for corporate sustainability has intensified. This study investigates the relationship between carbon emission intensity (CI) and corporate financial performance, measured by Return on Assets (ROA) and Tobin’s Q, while examining the moderating role of Science Based Targets initiative (SBTi) participation. Using panel data of 2,514 listed companies across 13 Asia-Pacific countries from 2016 to 2023, we employ a fixed-effects regression model with robust standard errors and control for firm size, leverage, growth, and year-sector-country fixed effects. Our findings indicate that higher carbon emissions negatively affect both profitability and market valuation. Although SBTi participation is positively associated with Tobin’s Q, its moderating effect on the emissions-performance relationship is not statistically significant. Subgroup analyses reveal that the negative effects of emissions are more pronounced in developing countries and non-carbon-intensive sectors, where SBTi sends a stronger market signal. The study contributes to the ESG-finance nexus by highlighting the importance of institutional and sectoral contexts. Limitations include the absence of Scope 3 data and long term SBTi tracking, which future research should address using dynamic panel models.